Pengembangan Handout Mikrobiologi Berdasarkan Hasil Penelitian Antagonisme Kapang Antagonis terhadap Kapang Patogen pada Tanaman Buah Naga (Hylocereus sp.) - Aziz Tanama; Utami Sri Hastuti; Abdul Gofur (Bioscientist : Jurnal Ilmiah Biologi, 2020)
This research aims to produce teaching materials in the form of valid and practical Microbiology handouts based on the research "Antagonism of Antagonistic Fungi against Pathogenic Fungi". This type of research is development research. This development research was carried out by following the instructional design stages with the ADDIE approach, which consisted of 5 stages, namely: Analyze, Design, Develop, Implement, and Evaluate. The data on the feasibility of handout teaching materials were obtained from the results of validation by microbiology material experts and teaching materials expert. While the handout readability test was conducted by respondent students of the Undergraduate Biology Education Study Program, FKIP, University of Muhammadiyah Malang. The results showed that the percentage of eligibility of handout material by material expert validators was 96.52% with very valid criteria with little improvement. The percentage of feasibility of handouts by teaching materials expert is 100% with very valid criteria. The percentage of readability test by respondent students was 90.10% with very high readability criteria. The results of this study indicate that the handout teaching material is very feasible and practical to be used by students / lecturers in microbiology learning activities on the material "Antagonism of Antagonistic Fungi against Pathogenic Fungi in Plants".